2015
DOI: 10.1002/ppul.23188
|View full text |Cite
|
Sign up to set email alerts
|

Preschool oscillometry and lung function at adolescence in asthmatic children

Abstract: In asthmatic children, preschool IOS is associated with spirometric lung function at adolescence, but the scatter is wide. Normal preschool IOS seems to indicate favourable lung function outcome, whereas in some individuals IOS could potentially be of clinical use, at a younger age than spirometry, to screen lung function deficits and increased risk for later lung function impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 33 publications
3
34
0
2
Order By: Relevance
“…Mathematical and image‐functional modeling postulate that heterogeneous constriction of the small airways results in a negative frequency‐dependence of resistance, whereas R5 reflects the resistive properties of both large and small airways . Clinical studies suggest that frequency dependence of resistance might be superior to R5 in distinguishing children with asthmatic symptoms or an uncontrolled disease from healthy subjects, and in predicting loss of asthma control and later lung function . Frequency dependence of resistance might, however, also be influenced by upper airway shunt properties and the viscoelasticity of respiratory tissues .…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical and image‐functional modeling postulate that heterogeneous constriction of the small airways results in a negative frequency‐dependence of resistance, whereas R5 reflects the resistive properties of both large and small airways . Clinical studies suggest that frequency dependence of resistance might be superior to R5 in distinguishing children with asthmatic symptoms or an uncontrolled disease from healthy subjects, and in predicting loss of asthma control and later lung function . Frequency dependence of resistance might, however, also be influenced by upper airway shunt properties and the viscoelasticity of respiratory tissues .…”
Section: Discussionmentioning
confidence: 99%
“…Spirometry may be limited however, in the preschool child and reflects primarily central airway disease, while studies have suggested that the PAW may also play a role in the development and control of asthma. Thus, Knihtila et al has recently reported that IOS findings of peripheral airway obstruction at ages 2- 7 years in asthmatic children were significantly related to abnormal post bronchodilator spirometry in those patients as adolescents, ages of 12-18 years (28) . Based on a negative predictive value of 98% the authors concluded that asthmatic children with normal preschool lung function are unlikely to have decreased lung function in adolescence.…”
Section: The Clinical Value Of Iosmentioning
confidence: 99%
“…PAI has been shown to be clinically related to airway hyper- reactivity, nocturnal asthma, exacerbations, steroid-resistant asthma, and fatal asthma (22) . However, PAI may be clinically relevant at all levels of asthma severity (23) , and control (24,25) , as well as predicting the persistence of childhood asthma into adulthood (26) , and potential loss of lung function with age (27,28) .…”
Section: Introductionmentioning
confidence: 99%
“…A Finnish study showed that IOS in 158 wheezing children at the age of 2–7 years accurately predicted flow‐volume spirometry results at 12–18 years of age . Increased baseline Rrs5 in IOS in that study was also related to a sixfold risk of pathologic post‐BD forced expiratory volume in one‐second in later flow‐volume spirometry .…”
Section: Discussionmentioning
confidence: 81%